1998
DOI: 10.1002/(sici)1520-6343(1998)4:2<121::aid-bspy5>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and structure of the protonated forms of meso‐tetraarylporphyrins in solution

Abstract: A comparative study of the spectral-luminescent properties (at 293 K and 77 K) of meso-tetrakis (o-tolyl)porphyrin (o-TTP) and meso-tetraphenylporphyrin (TPP ), and also meso-tetrakis(n-propyl)porphyrin (TPrP) in nonaqueous acid media has been carried out with the aim to reveal effects associated with the influence of methyl groups which hinder sterically the twist of the phenyl rings enhancing their conjugation with the macrocycle in acid medium. On the basis of the spectral data it is concluded that although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(88 citation statements)
references
References 0 publications
5
81
2
Order By: Relevance
“…[6][7][8][9] In this framework, essential progress has been achieved in the elucidation of the molecular conformation of diprotonated forms, [4][5][6][7][8][9][10][11][12][13][14][15] and the type and extent of macrocycle nonplanar distortions have been extensively discussed in terms of molecular flexibility, [7,9,15] the peripheral substitution pattern, [6,7,9,14,15] and the strength of intermolecular interactions with acid residues and other anionic species in solution. [14,16,17] The relationship between the molecular structure and macrocycle core acid-base equilibrium has been studied. [16,[18][19][20][21][22] Studies of the excited states properties of diprotonated porphyrins have revealed dramatic changes in the rates and channels of the excitation energy deactivation as compared with those for the free bases, and different mechanisms involved in these changes have been proposed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9] In this framework, essential progress has been achieved in the elucidation of the molecular conformation of diprotonated forms, [4][5][6][7][8][9][10][11][12][13][14][15] and the type and extent of macrocycle nonplanar distortions have been extensively discussed in terms of molecular flexibility, [7,9,15] the peripheral substitution pattern, [6,7,9,14,15] and the strength of intermolecular interactions with acid residues and other anionic species in solution. [14,16,17] The relationship between the molecular structure and macrocycle core acid-base equilibrium has been studied. [16,[18][19][20][21][22] Studies of the excited states properties of diprotonated porphyrins have revealed dramatic changes in the rates and channels of the excitation energy deactivation as compared with those for the free bases, and different mechanisms involved in these changes have been proposed.…”
mentioning
confidence: 99%
“…[14,16,17] The relationship between the molecular structure and macrocycle core acid-base equilibrium has been studied. [16,[18][19][20][21][22] Studies of the excited states properties of diprotonated porphyrins have revealed dramatic changes in the rates and channels of the excitation energy deactivation as compared with those for the free bases, and different mechanisms involved in these changes have been proposed. [6,15,16,[23][24][25][26] Much less is known about the molecular conformation and optical properties of monoprotonated forms of porphyrins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence quantum yields were determined using the standard sample method, using free base 5,10,15,20-tetraphenylporphyrin as a standard (Φ 0 fl =0.09 in air equilibrated toluene solution). [30] The sample concentrations were of the order of 1•10 -6 M and were determined spectrophotometrically based on known extinction coefficients. All the samples were prepared by dissolving the porphyrin powder in dichloromethane, and the mono-and diprotonated forms were obtained by titration of the free base porphyrin solutions with perchloric acid (HClO 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…The closed symbols indicate the corresponding data for the three species of Mes 4 measured in THF-TFA solutions. [28] The fluorescence quantum yields change due to the attachment of additional protons in the macrocyclic core, the formation of the saddle type macrocycle conformation, which is expected to show an enhanced rate of radiationless deactivation of the excited S 1 state, and the possibility of fluorescence quenching upon association of positively charged macrocyclic core and negatively charged acid residues. [10,34,36,37,53] in the case under consideration, the fluorescence quantum yields increase, indicating that quenching by the perchlorate counter ions is negligibly small (if any).…”
Section: Spectral-luminescent Properties Of Meso-tetraarylporphyrinsmentioning
confidence: 99%